Pengaruh Budaya Organisasi dan Kepercayaan (Trust) terhadap Komitmen Organisasi - Nur Haris Ependi; Sudirman Sudirman (LPPM STKIP Kusuma Negara, 2021)
The aim of this research was to study the influence of organization behavior, trust and organization commitment. The method used in this research was quantitative survey. Data survey was collected from 96 employees. Data analysis using path analysis. Based on hypothesis testing that has been done, it can be described as the following research findings: (1) there is a positive direct influence of organization behavior to organization commitment, (2) there is a positive direct influence of trust to commitment, (3) there is a positive direct influence between organization behavior and trust.